Pattern of mtDNA variation in three populations from São Tomé e Príncipe - Trovoada, MJ (2004)
We have analysed the matrilineal genetic composition of three self-reported ethnic groups from São Tomé e Príncipe (Gulf of Guinea), an African archipelago whose settlement begun in the late fifteenth century. Sequence data from the hypervariable segments I (HVS-I) and II (HVS-II) were obtained for 30 Angolares, 35 Forros and 38 Tongas. The repertory of mtDNA lineages in São Tomé e Príncipe denoted a fully African maternal pool, primarily arisen from a Central/Southwestern substratum. The absence of any lineages of putative European descent means that the European impact at the mitochondrial pool was virtually nil. Angolares showed a clear reduction of mtDNA diversity and a slight genetic differentiation relative to Tongas or Forros, whereas the latter two groups did not present any signs of genetic boundaries between each other. The data obtained here reinforce the depiction of genetic substructuring in São Tomé e Príncipe previously derived from Y-chromosome STRs. In addition, the crossing of mtDNA and Y-STR information led to the inference that the female mediated gene flow within the archipelago was less restricted than the male, a pattern that could be framed in the cultural traditions and socio-historical interactions among the groups.